2017
DOI: 10.1061/(asce)cc.1943-5614.0000743
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Reinforced Concrete T-Beams Strengthened in Shear with Externally Bonded CFRP Sheets

Abstract: An experimental investigation was undertaken into the effectiveness of unanchored and anchored externally bonded (EB) U-wrapped carbon fibre reinforced polymer (CFRP) shear strengthening for reinforced concrete T-beams at a range of realistic sizes. The T-beam sizes, geometry and reinforcement were chosen to reflect existing slab-on-beam structures with low levels of transverse steel shear reinforcement. Geometrically similar reinforced concrete Tbeams were tested across three sizes ranging from 360 to 720 mm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 8 publications
2
29
0
2
Order By: Relevance
“…A new bond strength model was proposed using a test database to predict the strengthening performance of the FRCM composite. Foster et al did an experimental investigation on reinforced concrete T-beams of varied sizes to determine the effectiveness of unanchored and anchored externally bonded U-wrapped CFRP [30]. Beams were subjected to three-point bending with a span to depth ratio of 3.5.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A new bond strength model was proposed using a test database to predict the strengthening performance of the FRCM composite. Foster et al did an experimental investigation on reinforced concrete T-beams of varied sizes to determine the effectiveness of unanchored and anchored externally bonded U-wrapped CFRP [30]. Beams were subjected to three-point bending with a span to depth ratio of 3.5.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several researchers compared the experimental and analytical flexural and shear capacities of different CFRP strengthened RC beams [21][22][23][24][25][26][27][28][29][30][31][32]37,38]. However, most of them [22,[26][27][28]37] found close analytical values when ACI 440.2R-08 [33] was used.…”
Section: Analytical Prediction Of Beam Capacitiesmentioning
confidence: 99%
“…eir research results indicated that the load magnitude during CFRP reinforcement process is an important indicator of the ultimate strength of reinforced concrete beams, while the ultimate strength of CFRP-strengthened concrete beams is basically the same even with small initial load. Experimental and analytical investigations were also carried out on the CFRP shear and flexural strengthened concrete beams [16,17]. e experimental data indicated that greater thicknesses of CFRP did not increase the shear capacity of specimens with no unanchored method, compared with both control and unanchored CFRP-strengthened beams.…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of advanced materials and innovative methods of analysis can provide engineers with an opportunity to deliver greater material efficiency and provide end users with a sustainable alternative to demolition and new construction. In recent years [7][8][9][10][11], the use of fibre reinforced polymers (FRPs) in retrofitting existing reinforced concrete structures has increased in popularity. This has typically been employed in strengthening highway bridges [12] due to the resistance of FRPs to corrosion from road de-icing salts.…”
Section: Introductionmentioning
confidence: 99%